Innovation Compact System Usage for Household Water Treatment: A Case Study on Water Quality in Coastal Central Java: 10.32526/ennrj/24/20250110 - Sulistiyani, Sulistiyani; Joko, Tri; Setiani, Onny; Darundiati, Yusniar Hanani; Rahman, Muhammad Auliya (Environment and Natural Resources Journal, 2025)
In many coastal regions of Central Java, Indonesia, access to safe drinking water remains limited owing to often contaminated groundwater sources. This study evaluated the performance of a compact household water treatment system integrating aeration, filtration, adsorption, and ultraviolet (UV) disinfection. Water samples from 15 wells across Kendal, Semarang, and Demak were tested for 13 parameters, including turbidity, total dissolved solids (TDS), color, ammonia, iron, manganese, dissolved oxygen (DO), and total coliforms, analyzed by ISO/IEC 17025-accredited laboratories. The treatment significantly improved water quality, reducing turbidity from 14.00 to 4.96 NTU (65%), TDS from 738.6 to 336.35 mg/L (54%), color from 21.93 to 9.15 TCU (58%), and ammonia from 1.82 to 1.02 mg/L (44%); meanwhile, DO increased from 5.48 to 8.24 mg/L (33%). The Drinking Water Quality Index scores of samples from 80% of the sites improved from “very poor” (>200) to “good” (<100), indicating untreated water transformation from non-potable to potable. However, microbiological safety remained a limitation, with total coliforms reduced by 52% (from 230 to 110 CFU/100 mL) but failing to meet the 0 CFU/100 mL standard. Therefore, additional heat treatment or UV contact time extension from 3 to 6 h is recommended to achieve full microbial compliance. This study demonstrates the effectiveness of the treatment system in significantly improving physical and chemical quality, while highlighting the need to optimize its microbial disinfection capacity. Its affordability and simplicity make it a promising decentralized solution for underserved communities.